2006
DOI: 10.1021/ja061429e
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Discrimination of Cryptochiral Saturated Quaternary and Tertiary Hydrocarbons by Asymmetric Autocatalysis

Abstract: Chiral discrimination of saturated hydrocarbons has been very difficult to establish, or has not been possible at all. The first chiral discrimination of cryptochiral 5-ethyl-5-propylundecane 1, that is, (n-butyl)ethyl(n-hexyl)(n-propyl)methane, a chiral saturated quaternary hydrocarbon, which is known to exhibit practically no detectable value of optical rotation between 280 and 580 nm, has been accomplished by asymmetric autocatalysis of pyrimidyl alkanol. The absolute configuration of 1 has been determined.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(48 citation statements)
references
References 19 publications
0
47
0
1
Order By: Relevance
“…We found that the chirality of the saturated quaternary hydrocarbon was successfully discriminated using asymmetric autocatalysis [120] . The asymmetric autocatalysis initiated by the chiral ( R ) -quaternary hydrocarbon using pyrimidine -5 -carbaldehyde 32 and i -Pr 2 Zn produced ( S ) -pyrimidyl alkanol 33 with 97% ee and 93% yield.…”
Section: Discrimination Of Cryptochirality In a Saturated Quaternary mentioning
confidence: 98%
See 1 more Smart Citation
“…We found that the chirality of the saturated quaternary hydrocarbon was successfully discriminated using asymmetric autocatalysis [120] . The asymmetric autocatalysis initiated by the chiral ( R ) -quaternary hydrocarbon using pyrimidine -5 -carbaldehyde 32 and i -Pr 2 Zn produced ( S ) -pyrimidyl alkanol 33 with 97% ee and 93% yield.…”
Section: Discrimination Of Cryptochirality In a Saturated Quaternary mentioning
confidence: 98%
“…In addition, various chiral hydrocarbons with such as saturated tertiary hydrocarbons [120] , 1,1 ′ -binaphthyls [121] , helicenes [122] , olefi ns [123] , allenes [124] , and [2.2]paracyclophanes [125] also serve as chiral initiators in this asymmetric autocatalysis.…”
Section: Discrimination Of Cryptochirality In a Saturated Quaternary mentioning
confidence: 99%
“…Racemic acetylthiophene 14 derived from 3-hexanone was resolved using HPLC with a chiral stationary phase into (R)-and (S)-enantiomers 14 with >99.5% ee. 25 The absolute configurations of 13 were determined from X-ray single-crystal analysis of 2,4-dinitrophenylhydrazone derived from (R)-14. Subsequent deoxygenative reduction, desulfurization, and hydrogenation gave the cryptochiral saturated quaternary hydrocarbons (R)-and (S)-13.…”
Section: Discrimination Of Cryptochirality In Saturated Quaternary Anmentioning
confidence: 99%
“…It was found that the cryptochirality of the saturated quaternary hydrocarbon 13 was successfully discriminated by the asymmetric autocatalysis with amplification of ee ( Figure 9). 25 That is, when asymmetric addition of i-Pr 2 Zn to pyrimidine-5-carbaldehyde 3 in the presence of chiral saturated quaternary hydrocarbon (S)-13, (R)-pyrimidyl alkanol 4 in high ee was formed after the amplification of ee by asymmetric autocatalysis. In contrast, asymmetric autocatalysis in the presence of (R)-13 gave (S)-alkanol 4.…”
Section: Discrimination Of Cryptochirality In Saturated Quaternary Anmentioning
confidence: 99%
“…The Soai reaction shows extreme sensitivity towards the chiral induction exerted by even very low quantities both of the autocatalyst [16][17][18][19][20][21][22][23][24] and of added (enantiomerically pure or enriched) "foreign" chiral molecules [25][26][27][28][29][30][31]. It has also been proved experimentally that such inductor molecules may include enantiomers of simple chiral organic compounds with chirality due only to stable isotopic substitution [32][33][34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%